Pemberdayaan Ekonomi Masyarakat Melalui Program Pendampingan Lembaga Keuangan Mikro Kewirausahaan - Anwar Muttaqin; Rohmanur Aziz (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2020)
This Paper aims to find out the Shafira Foundation LKMK mentoring process to carry out economic empeworment in helping people to have business capabilities according to their potential and have the capital to run their business. The form of empowerment is carried out in the form of assistance through coaching, providing capital, and business development. This study uses a descriptive method with a qualitative approach, the data collected is obtained from the results of observations, interviews, and documentation studies. The results of the research show that the LKMK mentoring process is good, because in the mentoring process not only providing capital, but the community will be given guidance by using the andragogical approach so that the spirit of the community in entrepreneurship can increase, and have the ability according to their potential. Providing business capital is carried out using the sharia economic business concept with a takaful system (mutual guarantee), after being given business capital the fostered partners will be assisted and directed by providing motivation, and business relations to be feasible, sustainable, and banknable.